Optimization of Indigenous Microorganism (IMO) Concentration in Chicken Feathers on the Physicochemical Properties of Feather Meal - Napitupulu, Monica Stephani; Novia, Deni; Sandra, Afriani (Andalasian Livestock, 2026)
This study aimed to evaluate the effect of adding indigenous microorganisms (IMO) derived from chicken feathers on the physicochemical properties of chicken feather flour, namely, color, microscopic structure, and crude fiber content. An experimental method with a completely randomized design (CRD) with five treatments and four replications was used in this study. The treatments were the addition of IMO chicken feathers at levels A (0%), B (1.5%), C (3%), D (4.5%), and E (6%) to fermentation feather meal. The parameters observed were color (L*, a*, b*), microscopic structure, and crude fiber content. The results showed that increasing IMO concentration significantly decreased lightness (L*), crude fiber content, and increased yellowness (b*) but did not significantly affect redness (a*). Microscopic observations revealed keratin structure degradation at higher IMO concentrations. The optimal concentration was 4.5%, resulting in balanced physicochemical properties of feather flour. These findings demonstrate the potential of IMO application for the sustainable utilization of chicken feather waste as a protein-rich feather meal.